POTTS, Annie; ARMSTRONG, Philip; BROWN, Deirdre. A New Zealand book of beasts: animals in our culture, history and everyday life - Vander Velden, Felipe F. (Cadernos de Campo (São Paulo, 1991), 2019)
Trata-se da resenha do livro: POTTS, Annie; ARMSTRONG, Philip; BROWN, Deirdre. A New Zealand book of beasts: animals in our culture, history and everyday life. Auckland: Auckland University Press, 2013, 288p., uma exploração da antropologia e da história cultural das relações entre humanos e animais na Nova Zelândia.